2002
DOI: 10.1111/j.1574-6941.2002.tb00936.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative diversity and composition of cyanobacteria in three predominant soil crusts of the Colorado Plateau

Abstract: Terminal restriction fragment length polymorphism (TRF or T-RFLP) analysis and 16S rDNA sequence analysis from clone libraries were used to examine cyanobacterial diversity in three types of predominant soil crusts in an arid grassland. Total DNA was extracted from cyanobacteria-, lichen-, or moss-dominated crusts that represent different successional stages in crust development, and which contribute different amounts of carbon and nitrogen into the ecosystem. Cyanobacterial 16S rRNA genes were amplified by PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 38 publications
3
56
0
1
Order By: Relevance
“…vaginatus was the dominant species in the ASCs, which was consistent with the results of Redfield et al [11]. The present study found that M. vaginatus was also the dominant species in all of the soil layers in the CLSCs and the soil layers below 1 mm in the GLSCs.…”
Section: Algae Composition and The Bsc Structuressupporting
confidence: 93%
See 3 more Smart Citations
“…vaginatus was the dominant species in the ASCs, which was consistent with the results of Redfield et al [11]. The present study found that M. vaginatus was also the dominant species in all of the soil layers in the CLSCs and the soil layers below 1 mm in the GLSCs.…”
Section: Algae Composition and The Bsc Structuressupporting
confidence: 93%
“…This result may be attributable to this alga's strong gliding ability and relatively large bodies [22]. Moreover, this result is different from those obtained in the LSCs, in which the dominant species M. vaginatus is replaced by other cyanobacteria [11]. In the GLSCs, S. javanicum dominated the top 1-mm soil layer, which may be closely related to this alga's strong resistance to UV radiance [29] and relative smaller swelling factor of the green algae-lichens, which prevents the thalli from completely covering the cracks between the lichen thalli.…”
Section: Algae Composition and The Bsc Structuresmentioning
confidence: 83%
See 2 more Smart Citations
“…With crust development and succession, dark-colored lichens or mosses later colonize the soil surface (Lange et al, 1992;Zaady et al, 2000;Lan et al, 2010a). Compared with cyanobacterial crusts, later successional lichen or moss crusts have the higher biological metabolic efficiency and protective ability; hence better topsoil microenvironments are expected in the later BSCs (Castenholz and Garcia-Pichel, 2000;Redfield et al, 2002;Housman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%